2014
DOI: 10.1177/0300985814532821
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Cat Factor XII Gene and Identification of a Mutation Causing Factor XII Deficiency in a Domestic Shorthair Cat Colony

Abstract: Coagulation factor XII (FXII) may be important in cardiovascular and inflammatory diseases. We have identified and characterized a naturally occurring mutation in the feline FXII gene that results in a mutant protein and enzymatic loss of activity. Feline intron/ exon gene structure and sequence were acquired by comparing DNA sequences obtained from a fragmented Felis catus genomic sequence and the National Center for Biotechnology Information's Cross Species Megablast of multiple species' FXII gene sequences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(62 reference statements)
2
5
0
Order By: Relevance
“…This difference suggests a geographical variation in distribution of feline F12 mutations. Additionally, the previously reported feline FXII mutation [1] and the c.1631G >C mutation of the present study were found in DSH cats. A survey of Feline FXII deficiency in the United States revealed that the trait was most commonly found in DSH cats, but that Siamese cats were apparently overrepresented in the study population [2].…”
supporting
confidence: 75%
See 3 more Smart Citations
“…This difference suggests a geographical variation in distribution of feline F12 mutations. Additionally, the previously reported feline FXII mutation [1] and the c.1631G >C mutation of the present study were found in DSH cats. A survey of Feline FXII deficiency in the United States revealed that the trait was most commonly found in DSH cats, but that Siamese cats were apparently overrepresented in the study population [2].…”
supporting
confidence: 75%
“…This novel mutation resulted in an amino acid substitution (p.G544A) and marked reduction in the amount of rfFXII protein secreted into transfected cell supernatants compared with that of wild-type transfectants. Notably, the c.1321delC, previously reported in DSH in the United States [1], was absent from all cats evaluated in our present study (Data not shown). The novel c.1631G>C mutation is therefore considered causative for FXII deficiency in the littermate DSH we studied.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…The variants also co-segregate, although variant c.1631G>C is likely to have originated first, as it is observed without the c.1321delC variant. These variants are both considered common in the domestic cat (25)(26)(27). The most severe aPTT prolongation is observed in cats homozygous for both variants (25).…”
Section: Genetic Epidemiology Of the Common Ab Blood Group System Across Breeds And Breed Typesmentioning
confidence: 99%